Seizure Diaries and Forecasting With Wearables: Epilepsy Monitoring Outside the Clinic - Brinkmann, Benjamin H.; Karoly, Philippa J.; Nurse, Ewan S.; Dumanis, Sonya B.; Nasseri, Mona; Viana, Pedro F.; Schulze-Bonhage, Andreas; Freestone, Dean R.; Worrell, Greg; Richardson, Mark P.; Cook, Mark J. (Frontiers in Neurology, 2021)
It is a major challenge in clinical epilepsy to diagnose and treat a disease characterized by infrequent seizures based on patient or caregiver reports and limited duration clinical testing. The poor reliability of self-reported seizure diaries for many people with epilepsy is well established, but these records remain necessary in clinical care and therapeutic studies. A number of wearable devices have emerged which may be capable of detecting seizures, recording seizure data, and alerting caregivers. Developments in noninvasive wearable sensors to measure accelerometry, photoplethysmography, electrodermal activity, electromyography, and other signals outside of the traditional clinical environment may be able to identify seizure-related changes. Ambulatory, non-invasive scalp EEG and minimally invasive subscalp EEG may allow direct measurement of seizure activity. However, significant network and computational infrastructure is needed for continuous, secure transmission of data. The large volume of data acquired by these devices necessitates computer-assisted review and detection to reduce the burden on human reviewers. Furthermore, user acceptability of such devices must be a paramount consideration to ensure adherence with long-term device use. Such devices can identify tonic-clonic seizures, but identification of other seizure semiologies with non-EEG wearables is an ongoing challenge. Identification of electrographic seizures with subscalp EEG systems has recently been demonstrated over long (>6 month) durations, and this shows promise for accurate, objective seizure records. While the ability to detect and forecast seizures from ambulatory intracranial EEG is established, invasive devices may not be acceptable for many individuals with epilepsy. Recent studies show promising results for probabilistic forecasts of seizure risk from long-term wearable devices and electronic diaries of self-reported seizures. There may also be predictive value in individuals’ symptoms, mood, and cognitive performance. However, seizure forecasting requires perpetual use of a device for monitoring, increasing the importance of the system’s acceptability to users. Furthermore, long-term studies with concurrent EEG confirmation are lacking currently. This review describes the current evidence and challenges in the use of minimally and non-invasive devices for long-term epilepsy monitoring, the essential components in remote monitoring systems, and explores the feasibility to detect and forecast impending seizures via long-term use of these systems.